Perspektif Hukum Islam terhadap Perlindungan Khusus bagi Pelapor dan Saksi Tindak Pidana Pencucian Uang - Faisal Fauzan; Bismi Khalidin; Ira Maghfirah (Media Syari'ah, 2021)
AbstractThis study aims to determine how the perspective of Islamic law on special protection for whistleblowers and witnesses is regulated in existing law in Indonesia, especially in Government Regulation No.57 of 2003 concerning Special Protection Procedures for Reporters and Witnesses to the Crime of Money Laundering. As normative juridical law research and is analyzed using descriptive-analytical methods, namely by analyzing the data under study by describing these data, then the conclusion is drawn. Special protection is a form of protection provided by the state to guarantee a sense of security for Reporting Parties or Witnesses from possible threats that endanger themselves, their lives, and/or their assets including their families. Criminal provisions in positive law, namely those regulated in Legislation Number 31 of 1999, for perpetrators who threaten and intimidate witnesses and whistleblowers can be subject to imprisonment and fines. In Islam, giving testimony is ordered directly in the Koran so that maintaining the safety of witnesses is also very important. The perspective of Islamic law on the form of special protection for whistleblowers and witnesses in criminal acts, in particular, the Crime of Money Laundering in positive law in Indonesia has met the values in the objectives of Islamic law (maqashid al-shari'ah). This is regulated in the Positive Law in Indonesia which regulates sufficiently the rights of a witness and also a whistleblower of a crime.AbstrakPenelitian ini bertujuan untuk mengetahui bagaimana perspektif hukum Islam terhadap perlindungan khusus bagi saksi dan pelapor yang diatur dalam hukum positif di Indonesia, khususnya Peraturan Pemerintah No.57 Tahun 2003 tentang Tatacara Perlindungan Khusus Bagi Pelapor dan Saksi Tindak Pidana Pencucian Uang. Penelitian ini termasuk penelitian hukum yuridis normative dan dianalisis dengan menggunakan metode deskriptif analitik yaitu dengan cara menganalisa data yang diteliti dengan memaparkan data-data tersebut, kemudian diperoleh kesimpulan. Perlindungan khusus adalah suatu bentuk perlindungan yang diberikan oleh negara untuk memberikan jaminan rasa aman terhadap Pelapor atau Saksi dari kemungkinan ancaman yang membahayakan diri, jiwa dan/atau hartanya termasuk keluarganya. Ketentuan pidana secara eksplisit diatur dalam Undang-Undang No.31 Tahun 1999, bagi pelaku yang melakukan ancaman dan intimidasi terhadap saksi dan pelapor dapat dikenakan pidana penjara dan denda. Perspektif hukum Islam terhadap bentuk perlindungan khusus terhadap pelapor dan saksi dalam tindak pidana, khususnya Tindak Pidana Pencucian Uang dalam hukum positif di Indonesia telah memenuhi nilai-nilai dalam tujuan syariat Islam (maqashid al-syari’ah). Hal ini secara terang diatur dalam Hukum Positif di Indonesia yang mengatur secara cukup hak daripada seorang saksi dan juga pelapor tindak pidana.